Implementation of grid-connected photovoltaic system with power factor control and islanding detection - Mekhilef, Saad; Rahim, N.A. (2004)
An approach to power factor control and islanding detection of a grid connected photovoltaic system using Field Programmable Gate Array (FPGA) is proposed. The proposed method has been tested through different situations, including the loss of the utility supply, and the deviation at the output of the inverter helps to detect islanding more effectively. Hardware design was constructed to validate the effectiveness of the approach proposed. Experimental results have been chosen to show the effectiveness of the proposed technique.